The motives of death in the artistic structure of short stories by M. Hvylovyi (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
This article provides an analysis of the novels of M. Khvylovyi. The main characters live in non-existent world of revolution, which is also the "Dreamland" and "country of explosions." The author gives to the main characters 'conflict-'social status, draws attention to the significant components of the existential contradiction between the desire for self-fulfillment and lack of perspective. In the early 20s they experience frustration and depression due to inability to be used to its potential. First of all, determined problems: emotional or physical death is the inescapable result of losing the confidence in the bright future.
Keywords: 'conflict-' social status; existential contradiction